Clinical Impact of Liquid Biopsy in Prostatic Cancer: A Literature Review - Mohamed Hussein; Hiba Ismail (International Journal of Advanced Health Science and Technology, 2023)
The most prev amost prev abstract alent solid tumor in men worldwide is prostate cancer. The need for biomarkers to guide management choices is critical given the frequency of prostate cancer and its relatively lengthy clinical course. Based on a patient's unique risk stratification, which considers pathologic characteristics from a prostate biopsy, prostate-specific antigen (PSA) level, imaging, and other patient factors, decisions about localized prostate cancer treatment options, such as active surveillance, surgical excision, or targeted radiation, are made. An attractive method for thorough cancer analysis is to use "liquid biopsies" made up of analytes from a peripheral blood draw. These methods can be used as prognostic and predictive biomarkers as well as ready tissue sources for molecular profiling during the course of a disease and are straightforward, safe, and simple to repeat. Researchers conduct an examination of articles that are in accordance with the issue to be studied. Articles used in literature review are obtained through  the  database  of  international  journal  providers  through  PubMed,  we  investigated eleven clinical studies and discussed what happened in these clinical studies and the extent of the effectiveness of liquid biopsy in  prostatic cancer, in one study there was relative impact of common circulating tumor DNA alterations on patient response to the most widely used large, randomize advanced prostate cancer. Other studies reported that ZNF660 methylation analysis can potentially help to stratify low-/intermediate-grade PCs into indolent vs. more aggressive subtypes. Another study found that tumor-derived biomarkers in platelets of CRPC patients enabled prediction of the outcome after abiraterone therapy with higher accuracy than baseline serum PSA or PSA response. One study reported that de novo positive CTC count after androgen deprivation therapy is probably due to a passive mechanism associated with the destruction of the tumor. In this review, we suggest that liquid biopsy could be used as biomarker for prostatic cancer, Further studies are needed to enhance liquid biopsy efficacy.